2022
DOI: 10.1063/5.0089989
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric transmission and coherent perfect absorption in a periodic array of thermoacoustic cells

Abstract: This paper describes some exotic scattering properties of a one-dimensional network of thermoacoustic cells and characterizes them experimentally. The considered two-port consists of a waveguide containing a periodic arrangement of porous materials subjected to temperature gradients and separated by empty sections. The interaction of an acoustic wave with the temperature gradients leads to an inherently nonreciprocal phenomenon known as the thermoacoustic effect. It is shown that this effect can be exploited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…It is found that spatial modulation of the real component of the permittivity could control the mode output, and the time modulation can be used to construct nonreciprocal devices such as optical isolators [20]. The coherent-perfectabsorption−laser point (CPA−LP) [21][22][23][24][25] and nonreciprocal amplification [26] can be realized by modulating the imaginary part of the dielectric constant. CPA−LP is the reverse physics process of a laser, which could be utilized for an anti-laser, and it may completely absorb the electromagnetic wave with a specific frequency and waveform.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that spatial modulation of the real component of the permittivity could control the mode output, and the time modulation can be used to construct nonreciprocal devices such as optical isolators [20]. The coherent-perfectabsorption−laser point (CPA−LP) [21][22][23][24][25] and nonreciprocal amplification [26] can be realized by modulating the imaginary part of the dielectric constant. CPA−LP is the reverse physics process of a laser, which could be utilized for an anti-laser, and it may completely absorb the electromagnetic wave with a specific frequency and waveform.…”
Section: Introductionmentioning
confidence: 99%